An Inspirational, Fashionable Force: Judith Druck, My Grandmother - Axel, Elisabeth (Disability Studies Quarterly, 2013)
The founder, President and Creative Director of Art Beyond Sight paints a portrait of her grandmother who inspired her work in this field. Key words: blind museum access, blindness, blind aesthetics.